The Art of Paper Cutting: Strategies and Challenges in Chinese to English Subtitle Translation of Cultural Items - Chai, William; Ong , Hui Yi; Amini, Mansour; Ravindran, Latha (Journal of Modern Languages, 2022)
Culture is a way of life and embodiment of civilizations that is expressed through a language. The transfer of culture is a significant aspect of audio-visual translation as translators deal with more than just the written texts on surface level. Translating culture-specific items on paper cutting is an intercultural communication. However, translating cultural items in subtitling could cause challenges and problems for translators during the translation process. In this qualitative study, the translation strategies and challenges were explored in the subtitling of a Chinese cultural documentary on the art of papercutting titled The Life of Paper-cutting (剪紙人生; Jiǎn zhǐ rén shēng) retrieved from YouTube. The original video was subtitled to identify the challenges in subtitling. The strategies and challenges were first identified and then the process was described. It was found that the most appropriate translation strategies were omission, direct transfer, equivalence, and adaptation. The analysis revealed that the challenges were mainly technical, cultural, and linguistic. The findings can be used as a guide to utilise the translation strategies effectively in subtitling translations of similar audio-visual products to tackle the challenges faced in the Chinese to English translation of culture-specific items.